Peran Citra Merek Dalam Memediasi Pengaruh Pemasaran Media Sosial Terhadap Niat Beli - Nurfaizi, Junita; Purnomo, Hadi (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
The purpose of this study is to determine the influence of Mie Endess Bangkalan social media marketing on the purchase intention of generation z consumers in Bangkalan City through their brand image. This study uses a quantitative method by collecting data through a questionnaire distributed using google forms on social media, the number of samples in this study amounted to 97 respondents calculated from the lemeshow formula and determined by purposive sampling technique. The results of the analysis of data processing using SPSS Version 30 showed that the social media marketing variable had a positive and significant effect on purchase intention and brand image, as well as the brand image variable on the purchase intention variable showed a positive and significant influence, while brand image in this study was proven to play a role in mediating the influence of social media marketing on purchase intent. These findings show the important role of social media marketing activities for businesses in shaping brand image and purchase intent and how the brand image can lead consumers to purchase intention.The purpose of this study is to determine the influence of Mie Endess Bangkalan social media marketing on the purchase intention of generation z consumers in Bangkalan City through their brand image. This study uses a quantitative method by collecting data through a questionnaire distributed using google forms on social media, the number of samples in this study amounted to 97 respondents calculated from the lemeshow formula and determined by purposive sampling technique. The results of the analysis of data processing using SPSS Version 30 showed that the social media marketing variable had a positive and significant effect on purchase intention and brand image, as well as the brand image variable on the purchase intention variable showed a positive and significant influence, while brand image in this study was proven to play a role in mediating the influence of social media marketing on purchase intent. These findings show the important role of social media marketing activities for businesses in shaping brand image and purchase intent and how the brand image can lead consumers to purchase intention.